The Impact of COVID-19 on Multidisciplinary Care Delivery to Children with Cerebral Palsy and Other Neuromuscular Complex Chronic Conditions - Hillary Brenda Nguyen; Neha Mulpuri; Danielle Cook; Michael Greenberg; M. Wade Shrader; Ryan Sanborn; Kishore Mulpuri; Benjamin J. Shore (MDPI AG, 2023)
The COVID-19 pandemic has caused unprecedented challenges in the care of children with cerebral palsy (CP) and other neuromuscular complex chronic conditions (NCCCs). The purpose of this study is to explore the direct impact of the COVID-19 pandemic on healthcare delivery. From May to August 2020, medical professionals caring for CP and NCCC patients across multiple countries and disciplines completed a self-administered cross-sectional survey comparing practices before and during the COVID-19 pandemic. Of the 79 healthcare workers from eight countries who participated-predominantly pediatric orthopedic surgeons (32%), pediatricians (30%), and pediatric physiatrists (23%)-most of them felt that caring for NCCC patients during the pandemic presented unique difficulties, and they reported a significant decrease in the in-person NCCC clinic volume (p < 0.001), multidisciplinary appointments (p < 0.001), surgical cases (p = 0.008), and botulinum toxin/phenol injections. Most providers affirmed that institutional guidelines for perioperative emergent/urgent and elective procedures, workplace settings, and technology were modified to accommodate the ongoing public health crisis. The usage of telemedicine significantly increased for NCCC patient visits (p < 0.001). During the COVID-19 pandemic, many children with NCCCs lost access to routine, multidisciplinary care. Telemedicine became an integral part of communication and management. In the setting of the COVID-19 pandemic and with the threat of future healthcare disruptions, these data lay the foundation for trending the evolution of healthcare delivery and accelerating best practice guidelines for children with CP and NCCCs.